2021
DOI: 10.1186/s12866-021-02220-3
|View full text |Cite|
|
Sign up to set email alerts
|

Human microbiota modulation via QseC sensor kinase mediated in the Escherichia coli O104:H4 outbreak strain infection in microbiome model

Abstract: Background The intestinal microbiota plays a crucial role in human health, adjusting its composition and the microbial metabolites protects the gut against invading microorganisms. Enteroaggregative E. coli (EAEC) is an important diarrheagenic pathogen, which may cause acute or persistent diarrhea (≥14 days). The outbreak strain has the potent Shiga toxin, forms a dense biofilm and communicate via QseBC two-component system regulating the expression of many important virulence factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Of interest, class Gammaproteobacteria increases in the bacteriota of antibiotic-treated mice ( Sekirov et al., 2008 ; Barreto et al., 2020 ), and animals are more prone to Salmonella enterica serovar Typhimurium infection ( Sekirov et al., 2008 ). Similar to our observations, mice infected with the tEAEC-STEC O104:H4 C227-11 strain had an imbalance of bacteriota, manifested as an increase in γ-Proteobacteria and Lactobacillus spp., with direct alteration in intestinal metabolites driven by microbiota changes ( Machado Ribeiro et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, class Gammaproteobacteria increases in the bacteriota of antibiotic-treated mice ( Sekirov et al., 2008 ; Barreto et al., 2020 ), and animals are more prone to Salmonella enterica serovar Typhimurium infection ( Sekirov et al., 2008 ). Similar to our observations, mice infected with the tEAEC-STEC O104:H4 C227-11 strain had an imbalance of bacteriota, manifested as an increase in γ-Proteobacteria and Lactobacillus spp., with direct alteration in intestinal metabolites driven by microbiota changes ( Machado Ribeiro et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the role of intestinal microbiota in pathogenic gastrointestinal infections allude that these organisms participate in the upregulation or downregulation of bacterial pathogen virulence (Menezes-Garcia et al, 2020;Wang et al, 2020;Cho et al, 2021;Machado Ribeiro et al, 2021; Shil The clustering correlation heatmap showed that there were differences in the abundance of many species of Klebsiella between KPLA and IKPLA (A). Furthermore, comparative analysis was performed for four members of the Klebsiella pneumoniae species complex (KpSC).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and rapid detection, characterisation and quantification of QSM can enhance our understanding of QS in various environments, as well as providing a real-time readout of microbial physiology within a given microbiome. Overview of representative bacterial quorum sensing systems: Escherichia coli cell illustrates an Autoinducer 3 (AI-3) Quorum Sensing (QS) system which regulates the locus of enterocyte effacement (LEE) pathogenicity island (Walters and Sperandio, 2006;Machado Ribeiro et al, 2021); an Autoinducing Peptide (AIP) system in Lactococcus lactis is presented, in which nisin has a dual role as a Quorum Sensing Molecule (QSM) and antimicrobial peptide (Kleerebezem, 2004); Vibrio fischeri cell illustrates the control of bioluminescence through an Acylated Homoserine Lactone (AHL) system also referred to as Autoinducer 1 (AI-1; Nealson, Platt and Woodland Hastings, 1970); Autoinducer 2 (AI-2) signalling is presented at the intersection due to its role in species-and genera-agnostic communications. The AI-2 biosynthetic pathway is highlighted in yellow alongside the Lsr/Lux pathways which provide for its internalisation/detection in various genera (Pereira, Thompson and Xavier, 2013).…”
Section: Methods For the Analysis Of Qsmmentioning
confidence: 99%